Biobutanol production from sulfuric acid‐pretreated red algal biomass by a newly isolated Clostridium sp. strain WK. (27th September 2019) - Hong, Ying; Chen, Chaoyang; Wu, Yi‐Rui
Abstract: Marine biomass, especially the algal biomass, is currently considered to be one of the most potential candidates for biofuels conversion during the development of biomass utilization. In this study, a diluted sulfuric acid pretreatment method was established for biobutanol from red algal biomass Gelidium amansii using a newly isolated Clostridium sp. strain WK. Under the optimal condition of 2% sulfuric acid treated in 20 Min at 131 °C, the maximal hydrolysis percentage of biomass can reach up to 80.95%, and the biobutanol production was obtained to be 3.46 g/L with a yield of 0.20 g/g after the fermentation of biomass hydrolysate. This result demonstrated a 12.5‐fold enhancement of conversion efficiency compared with the untreated control, which provides a new and efficient way to develop the biobutanol industry by utilizing the abundant, low cost, and carbohydrate‐rich algal biomass.